The detection of thermal windows in fossorial rodents with varied sociality degree - Vejmělka, František (Jihočeská univerzita, 2019)
Eight rodent species with fossorial activity differing in a number of characteristics such as ecology, climatic conditions, geographical distribution, or kinship were studied using infrared thermography in order to describe their surface temperature and its patterns. An attempt to describe the relation between surface temperature and varied social organisation in burrowing rodents was made.
The detection of thermal windows in fossorial rodents with varied sociality degree
Keywords: Fossorial; fur; heat dissipation; infrared thermography; mammals; mole-rats; rodents; thermal conduction; thermal insulation; thermal windows; social thermoregulation; sociality; solitary; subterranean; surface temperature; Fossorial; fur; heat dissipation; infrared thermography; mammals; mole-rats; rodents; thermal conduction; thermal insulation; thermal windows; social thermoregulation; sociality; solitary; subterranean; surface temperature